»Hochschulexperimentierplatz Bielefeld« – 50 Jahre Fakultät für Soziologie - Strulik, Torsten; Kruse, Volker (transcript, 2019)
This volume presents the 50-year history of the Bielefeld Faculty of Sociology from different perspectives and with a variety of personal and institutional references.